COMPARISON ANALYSIS OF ACCOUNTING-BASED BANKRUPTCY PREDICTION MODELS OF ALTMAN, SPRINGATE, ZMIJEWSKI AND GROVER IN PULP, PAPER AND WOOD FIRMS LISTED IN INDONESIA STOCK EXCHANGE (IDX) - admin, Gousantya Riustopo B42112002 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
There is a number of well-established and worldwide-known reliable method that could be used to detect bankruptcy. These prediction models could predict bankruptcy ahead of time, therefore, the firm might take actions to minimize possible risks and loss. This study compared some accounting-based prediction models which are Altman’s Z-score, Springate, Zmijewski and Grover model in pulp, paper and wood firms and analyzed the most significant accounting ratio of each model. The result shows that the most accurate prediction model is Grover (79,56%). Then, it is followed by Altman (74,49%), Zmijewski (73,05%) and Springate (55,92%). In addition, the significant accounting-ratio of each model is found by using pearson product moment correlation. Those significant ratio for Grover, Altman, Zmijewski and Springate respectively are working capital / total assets, market value of equity / book value of total liabilities, current assets / current liabilities and earning before tax / current liabilities. Key words: bankruptcy prediction model, accounting-based prediction model, Altman’s Z-score, Springate, Zmijewski, Grover.